Microwave synthesis of 5-Substituted 1H-Tetrazoles catalyzed by bismuth chloride in water - Coca, Adiel; Feinn, Liana; Dudley, Joshua (Synthetic Communications, 2015)
(Chemical Equation Presented). Bismuth chloride was used to catalyze the [2 + 3] cycloaddition between sodium azide with aryl nitriles, aliphatic nitriles, and vinyl nitriles. A number of 5-substituted 1H-tetrazoles were synthesized in water or isopropanol/water mixtures using microwave heating. Good yields were obtained for these reactions when heated for 1 h at 120-160°C in a 3:1 isopropanol/water mixture. A few of the less reactive nitriles required longer reaction times for good yields. © Taylor & Francis Group, LLC.
Keywords: 2 propanol; 5-substituted 1H-tetrazoles; Article; Bismuth chloride; [2+3] cycloaddition; acidification; bismuth derivative; carbon nuclear magnetic resonance; catalyst; chloride; cycloaddition; dept.che; micro-wave; microwave cooking; microwave radiation; nitrile; proton nuclear magnetic resonance; reaction time; sodium azide; solubility; synthesis; tetrazole derivative; vinyl derivative; water